Obstetric intensive care unit admission - clinical profile and outcome - a tertiary care hospital experience - Mufti, Asma Hassan; Wani, Nasir Jeelani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Intensive Care Unit (ICU) admission is on rise in pregnant women due to factors including increasing maternal age, increasing rates and levels of obesity and other comorbidities. The present study was done to analyze admission rate, outcome and trends in women requiring peripartum admission to ICU. Methods: In this retrospective study, peripartum admissions in obstetric ICU over the period of 6 months were studied. Demographics, comorbidities, diagnosis, ICU care, length of stay and outcome was analyzed. Results: Out of 7489 deliveries during the study period, a total of 112 patients were admitted to ICU. Thus, the rate of ICU admission in our study was 1.49%. Most of the patients belonged to 31-35 years age group (37.5%) and were multigravida (83.9%). Severe pre-eclampsia and eclampsia (77.7%) was most common diagnosis at time of admission in ICU.47.5% of patients required ventilatory support. Majority of patients (51.8%) had short (<3 days) stay of admission. Mortality during the study period was 4.5%. Conclusions: A multidisciplinary team approach including obstetrician and intensivist is appropriate in obstetric critical care units. Setting up of obstetric intermediate care units can lessen the burden. In addition to good antenatal care, timely referral, health education and training of health professionals may improve clinical outcome and better obstetric practice, especially in low resource countries like India.